Kompetensi yang Dibutuhkan Perawat Saat Bekerja di Ambulans Pra-Rumah Sakit: Scoping Review - Sanjana, I Wayan Edi; Widyandari, Ni Made Ayu Sukma; Agustini, Ni Luh Putu Inca Buntari (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Prehospital care has historically provided medical care with the aim of saving lives and preventing disability. Prehospital services that are accommodated by ambulances have complex and unpredictable care arrangements, so ambulance personnel, namely nurses, must prepare themselves to deal with all situations and conditions. This study aims to describe the competencies possessed by nurses while on duty in prehospital ambulances. This research is a literature study from several databases, and we obtained 20 articles for analysis. The results of the article analysis show that nurses who work in prehospital ambulances must have the competence to be able to save patients' lives, which is formed from knowledge, attitudes, and skills. Knowledge that must be possessed by ambulance nurses includes assessment, triage, and situation analysis. The positive attitudes of ambulance nurses include decision-making, communication, collaboration, caring, ethics, and culture. The skills possessed by ambulance nurses are BHD, intubation, examination of vital signs, interpretation of supporting examinations, and drug management. Ambulance nurses can improve their emergency care competencies through continuous education and training.